2021
DOI: 10.1136/thoraxjnl-2020-216586
|View full text |Cite
|
Sign up to set email alerts
|

Association of imbalance between job workload and functional ability with return to work in ARDS survivors

Abstract: BackgroundInability to return to work (RTW) is common after acute respiratory distress syndrome (ARDS). Mismatch in an individual’s job workload and his or her functional ability, termed work ability imbalance, is negatively associated with RTW, but has not been evaluated in ARDS survivors.ObjectWe examine associations between work ability imbalance at 6 months and RTW at 6 months and 12 months, as well as the ability to sustain employment in ARDS survivors.MethodsPreviously employed participants from the ARDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Patients with pain or fatigue were less likely to return to work [ 61 ]. At 6 and 12 months, the imbalance between occupational workload requirements and ARDS survivors’ functional ability occurred in 90% of ALTOS participants [ 62 ]. Furthermore, having imbalance in both physical and psychosocial areas at 6 months was significantly associated with joblessness at 6 and 12 months [ 62 ].…”
Section: Recent Data On Additional Aspects Of Picsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with pain or fatigue were less likely to return to work [ 61 ]. At 6 and 12 months, the imbalance between occupational workload requirements and ARDS survivors’ functional ability occurred in 90% of ALTOS participants [ 62 ]. Furthermore, having imbalance in both physical and psychosocial areas at 6 months was significantly associated with joblessness at 6 and 12 months [ 62 ].…”
Section: Recent Data On Additional Aspects Of Picsmentioning
confidence: 99%
“…At 6 and 12 months, the imbalance between occupational workload requirements and ARDS survivors’ functional ability occurred in 90% of ALTOS participants [ 62 ]. Furthermore, having imbalance in both physical and psychosocial areas at 6 months was significantly associated with joblessness at 6 and 12 months [ 62 ]. The findings from these studies highlight the need to improve patient’s functional abilities, and to decrease work load via workplace accommodations for ICU survivors [ 62 , 63 ].…”
Section: Recent Data On Additional Aspects Of Picsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Likewise, occupational therapy is another example of a key profession that would benefit from greater prevalence within services compared with the levels seen in the current findings, especially in the context of long-term cognitive impairment in critical illness survivors, [27][28][29] and the challenges of returning to work in this patient population. [30][31][32][33] Engagement with primary care reduced from inpatient to outpatient stages of management. Partnership with primary care is key to optimising quality of critical illness recovery 34 ; qualitative exploration of unplanned hospital readmission in ICU survivors highlights many contributing themes that primary care clinicians would be ideally placed to support during recovery, for example, multimorbidity, polypharmacy, inadequate social support and challenges with specialist equipment.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…133,[136][137][138][139][140] Kamdar and colleagues 139,140 have shown that 44% of previously employed survivors of ARDS were jobless at 1 year, and at 5 years 30% had never returned to work. Su and colleagues 141 found that one in five survivors of ARDS who had returned to work were subsequently unable to sustain work. In another study, Brown and colleagues 138 showed the percentage of survivors of ARDS living independently at home at 6 months reduced from a pre-existing baseline of 91% to 45% at 6 months.…”
Section: Sequelae Of Ardsmentioning
confidence: 99%